2021
DOI: 10.3389/ffgc.2021.660662
|View full text |Cite
|
Sign up to set email alerts
|

Bark-Water Interactions Across Ecosystem States and Fluxes

Abstract: To date, the perspective of forest ecohydrologists has heavily focused on leaf-water interactions – leaving the ecohydrological roles of bark under-studied, oversimplified, or omitted from the forest water cycle. Of course, the lack of study, oversimplification, or omission of processes is not inherently problematic to advancing ecohydrological theory or operational practice. Thus, this perspective outlines the relevance of bark-water interactions to advancing ecohydrological theory and practice: (i) across sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…There are also some studies linking bark structural properties to bark water dynamics (see Van Stan et al 2021 ). Loram-Lourenço et al (2020) studied the bark properties of 31 native tree species from Brazil and found that the relative investment in bark reflects different strategies of fire protection, and water use and conservation.…”
Section: Discussionmentioning
confidence: 99%
“…There are also some studies linking bark structural properties to bark water dynamics (see Van Stan et al 2021 ). Loram-Lourenço et al (2020) studied the bark properties of 31 native tree species from Brazil and found that the relative investment in bark reflects different strategies of fire protection, and water use and conservation.…”
Section: Discussionmentioning
confidence: 99%
“…The other parts of precipitation with contact to the canopy may be intercepted, building a short-term water storage pool, from which the three main water fluxescanopy interception, TF, and SFarise. Under certain conditions, water can also be absorbed by leaves and bark (Aubrey, 2020;Berry et al, 2019;Van Stan et al, 2021). Both meteorological factors and the canopy structure of forests affect rainfall partitioning.…”
Section: Introductionmentioning
confidence: 99%
“…Spatiotemporal variability of TF and its relation to forest structural variables have been reported for many tree species of various leaf traits and seasonal patterns (Chang and Matzner, 2000a;Kowalska et al, 2016;Loustau et al, 1992;Staelens et al, 2006b; and described in various models (André et al, 2011;Davie and Durocher, 1997a;Davie and Durocher, 1997b;Gerrits et al, 2010;Herbst et al, 2008;Loustau et al, 1992;van Dijk and Bruijnzeel, 2001a;van Dijk and Bruijnzeel, 2001b;Vrugt et al, 2003). Recent investigations documented correlations between SF volume and canopy structural traits like bark texture, diameter at breast height (DBH) and the height-to-width ratio of the as an indicator of the canopy geometry (Jiang et al, 2021;Tonello et al, 2021b;Van Stan et al, 2021) which might affect the TF due to lateral transport of precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Bark also plays important roles in forests as an intermediary between the outside environment and the inside of the tree, e.g. : hosting lichens and other corticolous epiphytic life, acting as an exchange site for aerosols and substances within precipitation, and being a pathway for rainfall that drains to the surface as stemflow (Van Stan et al, 2021). Stemflow may also be highly enriched in solutes, resulting in significant, locally concentrated nutrient inputs (Dovey et al, 2011;Germer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The external morphology of bark makes a significant contribution to the solute composition and concentration of stemflow, while the thickness and internal morphology of bark are also expected to affect the mechanisms of this bark-water solute exchange. Thus, the anatomical point of view is important for exploring the mechanism of stemflow chemistry (Levia and Herwitz, 2005;Van Stan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%